Machine Learning Enterprise Financial Intelligent Risk Control System Based on New Database - Guo, Hongyi; Liu, Yanjun; Hu, Ludong; Zhang, Xuanbo (International Journal of Global Economics and Management, 2024)
This article concentrates on the field of financial investment service technology and presents an intelligent enterprise financial risk control system based on the Milvus vector database with big data and machine learning. It employs algorithms such as random forest, Euclidean distance, and cosine similarity. Through a series of operations including meticulously designing the risk assessment system and developing the risk prediction system, it is committed to accurately analyzing and predicting risk situations such as cancellation or revocation that enterprises may face. This provides strong support for enterprise risk management and control, helps enterprises achieve sustainable development in the complex and changeable market environment, enhances enterprise stability and competitiveness, and strengthens the enterprise's ability to deal with risks, enabling them to make more effective strategic decisions and ensure long-term stability.